Prevalence of unintended pregnancy and associated factors among pregnant mothers in Jimma town, southwest Ethiopia: a cross sectional study - Girma Alemayehu Beyene (BMC, 2019)
Abstract Background Unintended pregnancy is a pregnancy that occurred when no children were desired or earlier than desired. One in three births in Ethiopia were unintended, which is major contributor to maternal morbidity and mortality. The objective of this study was to assess prevalence of unintended pregnancy and associated factors among pregnant women in Jimma. Methods Community based cross-sectional study was conducted from May to June, 2016. Estimated sample size of 356 was allocated proportionally to the randomly selected kebeles based on number of pregnant women in their kebeles and simple random sampling technique was used in selecting participants. Data were collected by structured questionnaires with face to face interview, analyzed by SPSS and multivariate logistic regression was fitted to identify factors independently associated with unintended pregnancy. Results The prevalence of unintended pregnancy among the study participants was 36.5% (95% CI: 31-42%), of which 97 (27.2%) were unwanted and 33 (9.3%) were mistimed. The most common reasons for failure to avoid unintended pregnancy were because they believed they were not fertile 54 (41.5%) and 26 (20%) became pregnant despite the use of contraceptive methods. Age of the mother over 35 years, lower educational status of the partner, higher family size, smaller number of children desired and less knowledge of modern contraceptive methods were independent predictors of unintended pregnancy. Conclusion The prevalence of unintended pregnancy was high in the study area and programs aimed at reducing unintended pregnancy should target older couple. In addition, improving educational status of the partner and knowledge of modern contraceptive methods is demanded.